Pengukuran Kualitas Produk Dengan Metode Statistical Process Control : Studi Kasus PT Difa Kreasi - Ahmad Faqih Syukri; Hadita Hadita (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
PT DIFA KREASI is a service company in the printing sector. Established in 1972 on the basis of an effort that started from National Publishers, who have been active since the beginning of independence, to have a modern offset industry. As the basis for the overall activities of PT DIFA KREASI and the commitment of all existing personnel to make PT DIFA KREASI an international standard business actor, it is very necessary to implement a Quality Management System. The aim of the research is to measure the quality of paperback type products using statistical process control methods. The research method used is a combination method of direct observation and interviews. The research results show that the statistical process control method is appropriate to use for measuring the quality of paperback type products. Based on the results of product quality measurements using control charts in the perfect bending process, it is controlled (uniform), while measurements in the printing process produce uncontrolled (non-uniform) data. Meanwhile, the biggest causes of defects in the printing and perfect bending processes are respectively dirty and melted glue.